2017
DOI: 10.1016/j.nlm.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory high-density EEG investigation of the misinformation effect: Attentional and recollective differences between true and false perceptual memories

Abstract: The misinformation effect, a phenomenon in which eyewitness memories are altered via exposure to post-event misinformation, is one of the most important paradigms used to investigate the reconstructive nature of human memory. The aim of this study was to use the misinformation effect paradigm to investigate differences in attentional and recollective processing between true and false event memories. Nineteen participants completed a variant of the misinformation paradigm in which recognition responses to true … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 76 publications
3
21
0
Order By: Relevance
“…1. Each test item was tested individually using a procedure utilized in our prior work involving these materials (Kiat & Belli, 2017). First, a partial sentence reinstated the context of the target event detail.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…1. Each test item was tested individually using a procedure utilized in our prior work involving these materials (Kiat & Belli, 2017). First, a partial sentence reinstated the context of the target event detail.…”
Section: Methodsmentioning
confidence: 99%
“…The primary studies linking attention to false memory susceptibility have been conducted by Tousignant, Hall, and Loftus (1986), Zaragoza and Lane (1998), Lane (2006), Rivardo et al (2011), and Kiat and Belli (2017). Tousignant et al (1986) showed that experimental manipulations and individual differences which increased the amount of time allocated towards reading misleading postevent misinformationa proxy measure for attentionwas associated with reduced levels of misinformation susceptibility.…”
Section: Attention and False Memorymentioning
confidence: 99%
See 3 more Smart Citations